2020
DOI: 10.3390/publications8010010
|View full text |Cite
|
Sign up to set email alerts
|

Change in Format, Register and Narration Style in the Biomedical Literature: A 1948 Example

Abstract: Scientific communication has evolved over time and the formats of scientific writing, including its stylistic modules, have changed accordingly. Research articles from the past fit a research world that had not been taken over by the internet, electronic searches, the new media and even the science mass production of today and reflect a reality where scientific publications were designed to be read and appreciated by actual readers. It is therefore useful to have a look back to what science looked like in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…The second observation is that, by 1990, more flexibility in inserting extra-textual content, e.g., tables or figures, was needed by the editors. It is known that older studies had a more limited iconography, due to the obvious technical restraints that authors had to endure [13]. However, the appearance and diffusion of personal computers made creating graphs and figures an easier task for researchers and scientific studies were progressively adorned with richer sets of figures, hence the need to find them a place on the page.…”
Section: Resultsmentioning
confidence: 99%
“…The second observation is that, by 1990, more flexibility in inserting extra-textual content, e.g., tables or figures, was needed by the editors. It is known that older studies had a more limited iconography, due to the obvious technical restraints that authors had to endure [13]. However, the appearance and diffusion of personal computers made creating graphs and figures an easier task for researchers and scientific studies were progressively adorned with richer sets of figures, hence the need to find them a place on the page.…”
Section: Resultsmentioning
confidence: 99%
“…Narration plays an important role in scientific communication [13], and yet it has been shown that biomedical articles have progressively moved away from a more narrative style of reporting [14]. Although it is difficult to establish standardized properties of narrativity, most scholars still regard the work of Gustav Freytag as substantially valid [15,16].…”
Section: Introductionmentioning
confidence: 99%